2018
DOI: 10.1515/sjpain-2017-0153
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive behavioral therapy for irritable bowel syndrome: the effects on state and trait anxiety and the autonomic nervous system during induced rectal distensions – An uncontrolled trial

Abstract: Abstract Background and aims: Irritable bowel syndrome (IBS), is a common multifactorial gastrointestinal disorder linked to disturbances in the microbe gut-brain axis. Cognitive behavioral therapy (CBT), in face-to-face format has showed promising results on IBS and its associated psychological symptoms. The present study explored for the first time if CBT for IBS affects the autonomic nervo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…20,21 It has been shown that cognitive behavioral therapy leads to improved IBS symptoms by directly modifying gastrointestinal-related cognitions and behaviors; improved anxiety or depression is regarded as secondary and there is no modification of autonomic nervous system activity in response to pain. [22][23][24][25] On the other hand, other treatment studies have shown that improvement of IBS symptoms correlates closely with reduction of depression or anxiety and, in 1 study, improved tolerance to rectal distension was associated strongly with improved depression. 4,[26][27][28][29] IBS is clearly an heterogeneous disorder and psychological treatments can only be optimized once we understand better the relationship between psychological factors and IBS symptoms.…”
Section: Introductionmentioning
confidence: 73%
“…20,21 It has been shown that cognitive behavioral therapy leads to improved IBS symptoms by directly modifying gastrointestinal-related cognitions and behaviors; improved anxiety or depression is regarded as secondary and there is no modification of autonomic nervous system activity in response to pain. [22][23][24][25] On the other hand, other treatment studies have shown that improvement of IBS symptoms correlates closely with reduction of depression or anxiety and, in 1 study, improved tolerance to rectal distension was associated strongly with improved depression. 4,[26][27][28][29] IBS is clearly an heterogeneous disorder and psychological treatments can only be optimized once we understand better the relationship between psychological factors and IBS symptoms.…”
Section: Introductionmentioning
confidence: 73%
“…The findings from the visual analysis of the baseline, treatment, and follow-up stages of gastrointestinal symptoms in these patients showed that short-term intensive dynamic psychotherapy has created significant, meaningful, and lasting improvement percentages. Several studies have examined the effectiveness of various psychotherapies, such as cognitivebehavioral (Edebol-Carlman et al, 2018) and compassionfocused therapies (Seyyedjafari, 2019), which have a different focus compared to the psychoanalytic school.…”
Section: Discussionmentioning
confidence: 99%
“…Other factors in patients with IBS were also assessed as they contribute to the disability, including the Stress Symptoms Rating Questionnaire (SSRQ) and PCS. Only one study found that following CBT, the SSRQ, which evaluates the stress caused by these symptoms, was not significantly lower than the baseline within the group [ 23 ]. The PCS was significantly reduced through treatment with CBT, with one study reporting that 76.9% of subjects had a greater than 70% reduction, indicating a decrease in pain associated with IBS [ 13 , 15 , 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…Jang et al observed that with CBT, there was a significant decrease in dysfunctional attitude scores, which indicated an overall reduction in dysfunctional attitudes toward their IBS [ 22 ]. There was also an improvement in the amount of stress concerning their IBS, with a significant improvement in the Perceived Stress Scale (PSS) scores [ 21 , 23 ].…”
Section: Reviewmentioning
confidence: 99%